Mechanical Properties and Biodegradability of Acid-soluble Chitosan-Starch Based Film - Rachmawati, Novalia; Triwibowo, Radestya; Widianto, Roni (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2015)
Chitosan-starch blend film showed desirable elongation and oxygen transmission rate (OTR) values and demonstrated rapid degradation in soil burial treatment. The incorporation of higher glycerol concentration lowered tensile strength but increased the amount of transmittable water vapour. The biodegradability of chitosan-starch based film was tested using soil burial test. Chitosan-starch blend films were able to degrade naturally at slightly similar period, ranging from 72â87 days. The addition of glycerol was likely contributed to the high Water Vapour Transmission Rate (WVTR) value which faster the biodegradability of the film in soil. Among different type of acid solutions, lactic acid is less preferable solution to dissolve chitosan as it produced film with poor mechanical properties compared to acetic and formic acid. Based on its mechanical limitation, the film can be used as a coating based film for certain type of fish product, especially product with high lipid content.